Studi Rasionalitas Penggunaan Obat Favipiravir pada Pasien Covid-19 di RSUD Harapan Insan Sendawar Kabupaten Kutai Barat Tahun 2021 - Teresia Delvi; Liniati Geografi; Clara Ritawany Sinaga (Pharmasipha : Pharmaceutical Journal of Islamic Pharmacy, 2022)
Corona Virus Disease 2019 (COVID-19) is an infectious disease caused by the SARS COV-2 virus. One of the antiviral groups that are often used worldwide for the treatment of COVID-19 is Favipiravir. Favipiravir use should be monitored because the accuracy of the drug will maximize the effect of therapy on the patient. Evaluation of Drug Use (EPO) of Favipiravir in terms of rationality needs to be done. Drugs that are not used rationally can cause side effects, the length of treatment will be longer, and even cause death effects in patients. The purpose of this study was to describe the characteristics of COVID-19 patients based on age, gender, and comorbidities and to find out the rationale for using Favipiravir inpatients at the HIS Hospital based on the criteria for the right diagnosis, the right patient, the right drug, the right dose, the right time interval for administration, appropriate duration of administration and clinical outcomes of COVID-19 patients (PCR, TCM, and antigen). This research is a type of nonexperimental research, the research was carried out in a descriptive evaluative way, and the data was collected retrospectively by looking at the medical record data. Determination of the rationale for using Favipiravir was carried out using the literature of the Indonesian COVID-19 Drug Informatorium edition 3, 100% correct patient, 100% correct drug, 100% correct diagnosis, correct dose 50.84%, correct duration of administration 61.01%, correct time interval administration of 81.35% and clinical outcomes (PCR (-) 74.57% %, TCM (-) 16.94%, and Antigen (-) 6.77%.